1990
DOI: 10.1111/j.1532-5415.1990.tb05702.x
|View full text |Cite
|
Sign up to set email alerts
|

Earlobe Crease and Atherosclerosis

Abstract: The association between earlobe crease (ELC) and coronary and aortic atherosclerosis in 100 autopsied men ranging in age from 50 to 79 years, who died free of vascular diseases or related conditions, was studied in conjunction with blood pressure and serum total cholesterol (TC) levels. Earlobe crease was graded and defined as groups 1, 2, and 3 according to the depth and length in both ears. The extent of atherosclerosis in the coronary arteries and aortas was visually graded. Coronary atherosclerosis was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
1
24
1
1
Order By: Relevance
“…Prior studies reported that the degree of ELC was related to the extent of coronary atherosclerosis, 13,15 and in the present study, the total ELC score tended to increase with the number of affected coronary vessels; however, the difference among the subgroups did not reach a statistically significant level. These associations or tendencies are not statistically significant because, at least in part, of the small sample size in this study.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Prior studies reported that the degree of ELC was related to the extent of coronary atherosclerosis, 13,15 and in the present study, the total ELC score tended to increase with the number of affected coronary vessels; however, the difference among the subgroups did not reach a statistically significant level. These associations or tendencies are not statistically significant because, at least in part, of the small sample size in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…The ELC score in each case represented the total points for both ears. 15 Bilateral ELC in the present study was defined as a score ≥3.…”
Section: Grading Of Elcmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators consider that the reason why the preferred sites of atherosclerotic lesions are located on the posterior wall of the thoracico-abdominal aorta is due to the presence of the intercostal arteries in the thoracic aorta and the lumbar arteries in the abdominal aorta on the posterior wall (2) . However, the existence of these arteries cannot account for the fact that the lesions are more severe in the region where the four major arteries branch off (3) . The present work could account for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…• C) using a very dilute suspension of a mixture of 50, 80, 115, 230, and 330 µm-diameter polystyrene microspheres (density ρ s = 1.06 g/cm 3 , Duke Scientific, Palo Alto, Calif., USA) in methyl salicylate containing ethanol at 5% by volume (density ρ = 1.16 g/cm 3 , viscosity µ = 0.026 g/cm sec) as a substitute for blood. After the aortic tree and the entire flow system were filled with the suspension, the fluid was subjected to steady flow through the aortic tree, and the flow rates in the ascending aorta and eight major branches of the aortic tree were set to their desired values by adjusting the height of the head tank and each collecting reservoir.…”
Section: Methodsmentioning
confidence: 99%